Ginsenoside Rg3 Adjunctively Increases the Efficacy of Gefitinib Against NSCLC by Regulating EGFR Copy Number - Xinyi Lv; Yuehan Song; Tianhua Liu; Dingdan Zhang; Xinpeng Ye; Qingqing Wang; Rongrong Li; Jiayi Chen; Shujing Zhang; Xue Yu; Chunying Hou (Pharmaceuticals, 2025)
Background: Lung cancer has the highest morbidity and mortality of all tumors, and the development of TKI drugs targeting EGFR activating mutations has brought lung cancer treatment into the targeted era. In view of their low efficacy and susceptibility to drug resistance, there is an urgent need to find strategies to increase their efficacy and reduce the incidence of drug resistance. Methods: In this study, we examined the distribution and probability of EGFR mutations in non-small cell lung cancer patients in the cBioPortal database and compared the survival prognosis of patients with normal and abnormal EGFR, NSCLC patients treated with and without TKI, and NSCLC patients with different EGFR gene copy numbers. We established a mouse lung cancer model and examined the histomorphological characteristics of lung tissues via hematoxylin and eosin staining. Additionally, changes in the copy number of the EGFR gene and its protein expression levels were detected using RT-qPCR and Western blotting. Furthermore, we quantified the concentration of the EGFR protein using ELISA. Results: We found no significant advantage of EGFR-TKI therapy over first-line chemotherapeutic agents in patients with EGFR-abnormal NSCLC. The reason for this may be related to the abnormal EGFR gene copy number; the higher the copy number increases, the worse the survival prognosis of the patients. In molecular biology experiments, we demonstrated that ginsenoside Rg3 down-regulated the copy number of 18, 19, 20, and 21 exons and protein expression of EGFR in lung adenocarcinoma cells. The results of in vivo pharmacodynamic assays confirmed that sequential administration of ginsenoside Rg3 with TKI drugs could achieve a gainful complementary effect. Conclusions: Ginsenoside Rg3 down-regulates the copy number of EGFR important exons in EGFR-mutant cells of lung adenocarcinoma and reduces EGFR protein expression, thus providing a high gainful complementary effect in combination with EGFR-TKI.